Fingerprint Metabolite of Miana (Coleus sp.) Leaf Infusion and Juice: Authentication Based on FTIR Spectroscopy and Multivariate Analysis - Syahruni, Reny; Umar, Abd. Halim; Matasik, Lois Christfani (agriTECH, 2024)
Miana (Coleus sp.) is a plant belonging to the Lamiaceae family and has been widely used in traditional medicine. Despite the potential of the plant, the quality and quantity of chemical components that can be extracted are dependent on various factors, such as varieties and extraction techniques. Therefore, this study aimed to discriminate miana based on varieties and extraction techniques as well as identify its marker functional groups. The 4 different leaf varieties of the plant, including purple, green, batik, and color combination were extracted using the infusion method, both with and without the addition of water. FTIR (Fourier transform infrared) fingerprint metabolite of each extract was then analyzed with IRPal 2.0 software for functional group interpretation and multivariate data analysis (PCA and PLS-DA) using MetaboAnalyst 5.0. The results showed that the chromatogram profile of all varieties and extraction techniques had similar patterns. The PCA (principal component analysis) score plot yielded a total PC value of 98.5%, which could effectively discriminate the samples. In addition, the O–H group’s VIP score value (greater than 1) was a significant functional group that characterized the samples. Based on these results, the combination of FTIR spectroscopy and multivariate analysis could be used to discriminate miana based on varieties and extraction techniques, as well as identify functional groups serving as marker.